Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1463-1318.2010.02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of high‐grade dysplasia in colorectal adenomas

Abstract: Aim  Colonoscopy to detect and remove polyps has contributed to a reduction in colorectal carcinoma. Three‐year follow up is recommended for patients considered to be at high risk (at least three adenomas, adenoma ≥ 1 cm, villous or high‐grade features). Our study focused on patients diagnosed with high‐grade dysplasia with regard to initial management and follow up. Method  A search of patients who had had endoscopic removal of a high‐grade adenoma was carried out. Patients with the following were excluded: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 20 publications
(21 reference statements)
2
29
0
3
Order By: Relevance
“…The HGDA patients, who were at very high risk of colorectal cancer, presented comparable levels of decanoic acid to the CRC patients. Moreover, even though such patients usually undergo endoscopic removal of the adenoma in order to reduce tumor progression, they remain at high risk of developing further high-grade dysplasia adenoma or carcinoma [28].…”
Section: Mcfas Level In Plasma Samplesmentioning
confidence: 99%
“…The HGDA patients, who were at very high risk of colorectal cancer, presented comparable levels of decanoic acid to the CRC patients. Moreover, even though such patients usually undergo endoscopic removal of the adenoma in order to reduce tumor progression, they remain at high risk of developing further high-grade dysplasia adenoma or carcinoma [28].…”
Section: Mcfas Level In Plasma Samplesmentioning
confidence: 99%
“…Just over 1% of adenomatous polyps <1 cm are malignant, whereas up to 40% of adenomas >2 cm are malignant 9 . Also in one study demonstrated that patients who have a colorectal adenoma > 1 cm with HGD may be at high risk of developing further adenomas with HGD or carcinoma 10 . In a recent study the authors showed that the factors that are associated most strongly with risk of advanced neoplasia are patient age and the number and size of prior adenomas 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Median size of the lowgrade adenomatous polyps (benign group) was 3.5 mm (SD 17.6, range 2-50 mm). Although it is common to define polyps greater than 10 mm as advanced adenoma together with high-grade dysplasia (HGD) polyps, only patients with HGD (n = 7) were included in the CRC group because these polyps have the biological characteristics of premalignant rather than benign tumors [17]. Median size of the high-grade adenomatous polyps was 22.5 mm (SD 5.3, range 18-30 mm).…”
Section: Patient Clinical Characteristicsmentioning
confidence: 99%